2012
DOI: 10.4314/ijbcs.v5i5.29
|View full text |Cite
|
Sign up to set email alerts
|

Caractérisation physico-chimique et évaluation du risque d’eutrophisation du lac Nokoué (Bénin)

Abstract: Tél : 00229 96 63 81 24 RESUME L' étude, menée sur deux (2) ans (2006 et 2007) , a permis de faire le bilan hydrologique du lac Nokoué et de connaitre la qualité physico-chimique des eaux du lac en vue d'offrir les éléments de base pour une modélisation écologique future du système. Les données historiques observées au niveau des stations de Bonou et de Sô -Ava, de même que des mesures ponctuelles des débits à l'ADCP des tributaires à leurs entrées dans le lac, ont été exploitées pour réaliser ce bilan hydrolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 5 publications
1
20
1
3
Order By: Relevance
“…This is due to evapotranspiration in the dry season, resulting in a high concentration of nitrates compared to the rainy season. These nitrate contents are similar to those obtained by Mama et al (2011) in Lake Nokoué (Benin). The NH 4+ contents (0 to 0.36 mg / L) were low, they are far lower than those recorded in the Municipal Lake of Yaoundé, a lake qualified as eutrophe (Zébazé Togouet, 2008 and2011).…”
Section: -1-1-physico-chemistry Of the Waters Of Lake Lérésupporting
confidence: 88%
“…This is due to evapotranspiration in the dry season, resulting in a high concentration of nitrates compared to the rainy season. These nitrate contents are similar to those obtained by Mama et al (2011) in Lake Nokoué (Benin). The NH 4+ contents (0 to 0.36 mg / L) were low, they are far lower than those recorded in the Municipal Lake of Yaoundé, a lake qualified as eutrophe (Zébazé Togouet, 2008 and2011).…”
Section: -1-1-physico-chemistry Of the Waters Of Lake Lérésupporting
confidence: 88%
“…On the other hand, these values are very low compared to those obtained by Tapsoba et al (2016) with an average value of nitrates (5.3 mg / l) during the various months of their study, also low compared to those found by Mama et al (2011) andSomé et al (2008), which found values of 7 mg / l.…”
Section: Discussioncontrasting
confidence: 47%
“…En effet, la prolifération des plantes aquatiques est à l'origine de la formation d'un écran en surface des eaux qui empêche l'oxygénation du milieu. De plus la décomposition de ces plantes, induit une augmentation de la quantité de matière organique dans le milieu dont la dégradation favorise l'asphyxie des espèces halieutiques (Mama et al, 2011). La production de sulfure et de nitrite (substances toxiques) inhibent le développement d'autres producteurs primaires et des poissons à grande sensibilité.…”
Section: Discussion Et Conclusionunclassified